AD GLORIAM DEI: PATTERNS OF PAIN, SUFFERING AND PLEASURE IN MEDIEVAL CULTURE - Luibyva, Mariia-Milana (Ukrainian Cultural Studies, 2023)
The article provides a cultural analysis of the triad of pain, punishment and pleasure as a significant component of medieval religious practices and their representations. The artistic and visual sphere of medieval culture is characterized by the hegemony of images of violence. Accordingly, the study attempts to identify the potential of portraying violence to generate and legitimize various forms of pleasure. Violence in the religious discourse of the Middle Ages and its representations operates on several different levels: the pleasure associated with identifying with the victim, the pleasure of projecting cruelty on the tormentors, the pleasure of fantasizing about ritual violence against the sacred victim. Comparing the mechanisms of pain gratification in religious practices and masochism sheds light on the symbolic load and functions of pain in Medieval Culture. Medieval images of pain as a tool of punishment did not just reflect cruel realities: and images were common because they were motivated and created by certain types of pleasure. Artistic images of pain and suffering do not just depict broken bodies and psyche, they also create opportunities for constructing the "I", institutions and ideas in the interests of a whole range of different programs and ideological positions. The hegemony of violence in the visual art of the era has the potential to create a space for the cultivation of broader, subversive possibilities: compassion and opposition to the pain of martyrs, fantasies of resistance, emancipation, the formation of alternative forms of eroticism, getting voyeuristic pleasure from hurting others. The paper attempts a transcultural comparison of the practices of getting pleasure from causing pain on the example of religious practices (self-harm) and masochism: they are based on dramatic expectation, postponement, delay in final satisfaction, investment in fantasy, attraction to exhibitionism. Using masochism as an interpretive category, one can see the structures of fantasy, tension, and view that formed the basis of certain genres of medieval representation. Through fantasy, obscurity, and exhibitionism, masochism transcodes the body in pain to the scene of erotic liberation. With the help of a similar trio of techniques, martyrdom forms the sublime body of a saint.